Příprava a vlastnosti belitického slínku - Havlík, Leoš (Vysoké učení technické v Brně. Fakulta stavební, 2019)
DIPLOMOVÁ PRÁCE SE ZABÝVÁ PŘÍPRAVOU A VLASTNOSTMI BELITICKÉHO SLÍNKU. PODKLADEM K VYPRACOVÁNÍ TÉTO PRÁCE BYLO ZPRACOVÁNÍ VĚDECKÝCH ČLÁNKŮ NA DANÉ TÉMA FORMOU REŠERŠE, A STUDIUM DOSAŽENÝCH VÝSLEDKŮ VÝZKUMŮ PROVÁDĚNÝCH NA ÚSTAVU THD V BRNĚ. V RÁMCI EXPERIMENTÁLNÍ PRÁCE BYL PROVEDEN NÁVRH SLOŽENÍ SUROVINOVÉ MOUČKY K VÝPALU BELITICKÉHO SLÍNKU ZA PŘÍTOMNOSTI UHLIČITANU A SÍRANU DRASELNÉHO K MODIFIKACI SUROVINOVÉ MOUČKY. ÚČELEM MODIFIKACE SUROVINOVÉ MOUČKY JE POTENCIONÁLNÍ ZVÝŠENÍ REAKTIVITY BELITICKÉHO SLÍNKU. DÁLE BYLY PROVEDENY EXTRAKCE BYPASSOVÝCH ODPRAŠKŮ Z TUZEMSKÉ CEMENTÁRNY. VYHODNOCENÍ TOHOTO VÝZKUMU BYLO PROVEDENO METODOU X-RAY DIFRAKČNÍ (XRD) ANALÝZY.

DIPLOMA THESIS IS FOCUSED ON THE PREPARATION AND PROPERTIE OF BELITE CLINKER. IT IS BASED ON THE STUDY OF SCIENTIFIC ARTICLES DEALING WITH THE ABOVE MENTIONED TOPIC AS WELL AS THE ANALYSIS OF THE BRNO THD INSTITUTE´S RESEARCH RESULTS. AS PART OF MY EXPERIMENTAL WORK, A PROPOSAL OF THE COMPOSITION OF RAW MEAL TO EXTRACT BELITE CLINKER IN THE PRESENCE OF POTASSIUMS CARBONATE AND SULPHATE WAS MADE TO MODIFY RAW MEAL. THE PURPOSE OF MODIFYING RAW MEAL IS A POTENTIAL INCREASE IN BELITE CLINKER REACTIVITY. FURTHER THE EXTRACTION OF BYPASS DUST FROM A LOCAL CEMENT PLANT WAS CONDUCTED. THE EVALUATION OF THIS RESEARCH WAS MADE BY THE X-RAY DIFFRACTION (XRD) ANALYSIS METHOD.
Preparation and Properties of Belite Clinker
Keywords: BELIT; BELITICKÉ CEMENTY; AKTIVACE BELITU; DIKALCIUMSILIKÁT; FÁZOVÉ SLOŽENÍ; HYDRATACE SLÍNKOVÝCH MINERÁLŮ.; BELITE; BELITE CEMENTS; ACTIVATION OF BELITE; DICALCIUM SILICATE; PHASE COMPOSITION; HYDRATION OF CLINKER MINERALS.